Prevalence of brucellosis and associated risk factors in dairy cattle in Maekel and Debub Regions, Eritrea - Efrem, Ghebremeskel Habteyohannes; Mihreteab, Bereket; Ghebremariam, Michael K.; Okbamichael, Tekeste; Ghebresilasie, Yosief; Mor, Siobhan M.; Mamo, Gezahegne (Frontiers in Veterinary Science, 2023)
Introduction Brucellosis is a zoonotic disease with worldwide distribution. It is considered endemic in Eritrea, however, the current prevalence status and related risk factors in animals are unknown. The objective of this study was to determine the prevalence of and risk factors for brucellosis in dairy cattle in Maekel and Debub regions, Eritrea. Methods A cross sectional study was conducted between August 2021 and February 2022. A total of 2,740 dairy cattle from 214 herds in 10 sub-regions of Eritrea were selected for blood and data collection. Blood samples were tested using Rose Bengal Plate Test (RBPT) and positive samples were confirmed using competitive (c-ELISA). Data on risk factors was collected using questionnaire and analyzed using logistic regression. Results In total, 34/2740 animals tested positive by RBPT. Of these, 29 were confirmed positive by c-ELISA, giving an apparent and estimated true individual-level prevalence of 1.1% (95% CI: 0.7, 1.5%) and 1.3% (95% CI: 0.9, 1.8%), respectively. Sixteen herds (7.5%) tested positive by RBPT and of these 15 herds (7.0%) were confirmed positive by c-ELISA, giving an estimated true herd-level prevalence of 7.0% (95% CI: 4.0, 10.7). Animal and herd-level apparent prevalence was 1.6 and 9.2% in Maekel, while in Debub it was 0.6 and 5.5%, respectively. Multivariable regression analysis indicated that non-pregnant lactating cows (adjusted odds ratio [aOR] = 3.35; p = 0.042) were more likely to be Brucella sero-positive. History of abortion on the farm (aOR = 5.71; p = 0.026) and larger number of cows in the herd (aOR = 1.14; p < 0.001) were associated with brucellosis sero-positivity in herds. Conclusion Brucellosis prevalence was low in the study areas. Nonetheless, this low prevalence may increase if the disease is not controlled. Therefore, testing animals before movement, good farming practices, sanitary measures, and an awareness raising program on brucellosis are recommended.